HUMAN RESOURCES MAPPING OF CUPAK JOMBANG TOURISM VILLAGE - Siti Mujanah; Tri Ratnawati; Gustaf Naufan Febrianto (SEAN Institute, 2022)
This research was conducted with the aim of formulating a mapping of Human Resources in order to support the development of tourism in Cupak Jombang village. This research was conducted using a descriptive method to obtain a map of Human Resources consisting of identification of gender, age, educational background, work experience and competencies possessed by the people of Cupak Jombang. Data collection was carried out through a survey with a questionnaire instrument for the community to support the growth of tourism villages in Cupak Jombang. After the data is collected, it is analyzed using descriptive analysis. The results showed that most of the respondents in this study were 49.65% male and 50.35% female, aged 20-70 years, on average had secondary and lower education and most worked in agriculture and entrepreneurship. Furthermore, respondents have competence in the field of business and business of mat craftsmen, and they are experts, because this work has been occupied for a long time and requires special expertise. They were very enthusiastic when their village was developed into a tourist village and are willing to play an active role and take part in their respective fields. They also want some training in managing a tourist village, and other training such as planting and caring for agriculture, marketing training, culinary, catering and so on. because this work has been occupied for a long time and requires special expertise. They were very enthusiastic when their village was developed into a tourist village and are willing to play an active role and take part in their respective fields